Improvement of Interfacial Shear Strength of Mendong Fiber (Fimbristylis globulosa) Reinforced Epoxy Composite Using the AC Electric Fields - Heru Suryanto; Eko Marsyahyo; Yudy Surya Irawan; Rudy Soenoko; Aminudin (International Journal of Polymer Science)
The effects of the AC electric field treatment on the interfacial shear strength of mendong fiber-reinforced epoxy composites were investigated. For this purpose, the epoxy (DGEBA) with a cycloaliphatic amine curing agent was treated by the AC electric field during the curing process. The heat generated during the epoxy polymerization process was monitored. Structure of the epoxy was studied by X-ray diffraction, Fourier transform infrared spectroscopy (FTIR), and Scanning Electron Microscope, respectively. The interfacial shear strength (IFSS) was also measured using a single fiber pull-out test. XRD analyzes indicated that the treatment of AC electric fields was able to form a crystalline phase of epoxy. IFSS of the mendong fiber-reinforced epoxy composites was optimum increased by 38% in the AC electric fields treatment of 750 V/cm.